Microwave ring resonator based on thermoplastic substrate for chicken breast meat quality identification application - Manab, Nurul Hanani (2021)
In this study, the resonant method was applied to develop a single-port microwave ring resonator (MRR) based on the thermoplastic substrate for meat quality identification. Recently, the quality of meat, especially chicken meat, has sparked an interest in both the producers and the consumers, due to the increasing trend of consumption of chicken meat as one of the primary foods in Malaysia. Thus, the characterisation of chicken meat quality is required, especially in terms of water holding capacity (WHC). Hence, the chicken breast meat (CBM) was chosen as the material under test (MUT) for the MRR. In addition, the substrate for the MRR was made from polylactic acid (PLA), which is known as a natural and environmentally friendly material. The development of the MRR started by preparing the PLA substrate using a hot press machine, and the PLA substrate’s dielectric properties were identified using the open-ended coaxial probe method. Then, the CBM’s dielectric properties were extracted from the open-ended coaxial probe method, where these values were applied in the simulation for the MRR design. From the results, the PLA substrate’s dielectric constant (ε′) and loss tangent (tan δ) were found to be 2.26 and 0.0001 at 1.1 GHz, respectively, while ε′ for the fresh CBM was 55.23 and ε′ for the aged CBM was 49.43. The MRR was designed at 1.1 GHz and simulated between 1 GHz to 1.2 GHz. The newly developed MRR showed a good agreement for both methods (simulated and measurement) with minimum S11 (–26.67 dB and –20.18 dB), 3dB bandwidth (0.018 GHz and 0.02 GHz) and Q-factor (122.22 and 110). From the results of the simulation and the measurement of the MRR overlaid with the CBM, the Q-factor showed a good agreement as well, where the aged CBM showed a higher Q-factor (37.93 and 31.42) compared with the fresh CBM (18.96 and 22.0) due to the decrease in the water holding capacity (WHC) of the CBM. Therefore, it can be concluded that Q-factor (20), S11 (–7 dB) and 3dB bandwidth (0.1 GHz) can be used as thresholds to indicate the freshness of CBM.